Multiple scattering reduction in instantaneous gas phase phosphor thermometry: applications with dispersed seeding. (10th April 2019) - Stephan, Michael; Zentgraf, Florian; Berrocal, Edouard; Albert, Barbara; Böhm, Benjamin; Dreizler, Andreas
Abstract: In this study the structured laser illumination planar imaging (SLIPI) technique is combined with gas phase phosphor thermometry to measure quasi-instantaneously two-dimensional temperature fields with reduced bias from multiple scattering. Different reconstruction strategies are implemented, evaluated and compared, including a two-pulse and one-pulse SLIPI approach. A gradient-based threshold algorithm for particle detection is applied to conventional planar light sheet imaging as an alternative to reduce the bias caused by multiple scattering in seeding-free regions. As a demonstration, measurements are performed in a canonical flow configuration, consisting of a heated, turbulent, air jet surrounded by an ambient co-flow. Both air flows are seeded with the thermographic phosphor BaMgAl10 O17 :Eu 2+ . Conventional light sheet imaging in the context of gas phase phosphor thermometry suffers from multiple scattering causing a significant temperature bias and low temperature sensitivity. Applying the gradient threshold algorithm removes areas without any seeding particles which improves accuracy, precision and temperature sensitivity. However, multiple scattering influences are still present and may cause an increasing bias particularly for higher seeding density. One pulse (1p) SLIPI exhibits high accuracy at intermediate precision. Multiply scattered luminescence is not fully removed and spatial resolution is lowered. Two pulse (2p) SLIPI is recommended for high temperature sensitivity and accuracy, removing impact of multiple scattering furthermost. However, 2p-SLIPI exhibits reduced temperature precision.